ASAP YANG DI PERDAGANGKAN: KETIKA NIKOTIN BERTEMU DENGAN HUKUM SYARI’AH - Hana Rofifah; Nilla Sari; Fatmah Taufik Hidayat (PT. Hasba Edukasi Mandiri, 2026)
This article examines the phenomenon of cigarette and vape trade as nicotine-based products from the perspective of Islamic law (Sharia). The study focuses on analyzing the legal status of both consumption and commercial transactions involving cigarettes and vape, considering fundamental principles of Islamic jurisprudence such as public interest (maslahah), harm prevention (mafsadah), and the legal maxim “la darar wa la dirar” (no harm shall be inflicted or reciprocated). This research employs a qualitative method with a normative approach through the study of classical and contemporary literature. The findings reveal اختلاف scholarly opinions regarding the permissibility of cigarettes and vape, ranging from permissible (mubah), disliked (makruh), to prohibited (haram), depending on their health and social impacts. In the context of trade, the legality of selling such products is also influenced by the evaluation of their potential harm and benefit. The article concludes that as scientific evidence on the dangers of nicotine becomes more substantial, the tendency of Islamic legal rulings shifts toward prohibition, both in consumption and distribution.